Controllable Release and High‐Efficiency Collection of Hydrogen Peroxide: Application on the Quantitative Investigation of Biomolecule Oxidation Induced by Reactive Oxygen Species. Issue 7 (30th June 2014) - Hou, Yuting; Xin, Ningning; Chen, Shu; Deng, Chunyan; Xiang, Juan
Abstract Hydrogen peroxide and hydroxyl radical, both important members of the reactive oxygen species (ROS) family, can cause serious oxidative damages in biological systems. In order to proclaim and prevent oxidation stress, researches on the biomolecule oxidation induced by H2O2 or OH. are in crucial need. However, due to the high reactivity of ROS, traditional methods are difficult to achieve the in situ quantitative investigations on those reactions involving ROS. In this work, using scanning electrochemical microscopy technique (SECM) in a tip generation‐substrate collection mode (TG‐SC), the controllable release and the high‐efficiency collection of electrogenerated H2O2 were achieved. Compared to ex situ fluorescence method, SECM improved the collection efficiency approximately two times larger. Based on it, SECM combined with surface plasmon resonance (SPR) was employed to in situ monitor the protein oxidation (taking Cu12+MT as a model) induced by H2O2. OH., which was generated from the interaction between H2O2 and Cu12+MT, can attack the peptide chain and induced the unrepairable protein oxidation damage. The whole process was quantitatively characterized by SPR, and the linear relationship between SPR dip shift and the amounts of released H2O2 was successfully built. Our work proves that the combined SECM‐SPR technique can realize the in situ quantitative determinations of the biomolecule oxidation induced by ROS, which affords an avenue for further elucidation on the mechanisms of oxidation stress in organisms.